PENGEMBANGAN MODUL BERBASIS CONTEXTUAL TEACHING AND LEARNING UNTUK MATERI BARISAN DAN DERET KELAS X SMK NEGERI 4 PADANG - Desvita, Vivi - (Pendidikan Matematika, 2014)
The development research is motivated by the of texsbooks used by students in the learning of mathematics. Textbooks used can not provide the opportunity for students to construct their own understanding. Attemps to overcome these problems by developing a valid and practical module based contextual teaching and learning in the matter of sequence and series. The model of development is four-D. Four-D includes four phases: definition, design, develope and dessiminate. The research only until the development stage. At this stage of development do the validation and practicalities. Validation results are very valid. Based on the results carried out on the practicalities of teachers and students expressed very practicalities module.